Improving of copper extraction from chalcopyrite by using NaCl - Turan, M. Deniz; Boyrazli, Mustafa; Altundogan, H. Soner (Journal of Central South Univ, 2018)
The addition of NaCl in the ammonium persulfate-APS (as an oxidant) leaching was investigated. APS has some advantages compared with conventional oxidants and its standard redox potential (EA degrees) is 2.0 V. Effect of six parameters such as NaCl concentration, APS concentration, temperature, time, liquid-solid ration (L/S), and stirring speed on the leaching behavior was studied. Results showed that metals extraction increased with increasing of NaCl concentration, APS concentration, leaching temperature (up to 333 K), and L/S ratio. During oxidative leaching of sulfide minerals, the occurrence of elemental sulfur layer on particle surface is known as primary problem that causes low metal extraction. According to the results, the passivation effect of sulfur layer and low dissolution problems can be eliminated in the presence of chloride ions. Copper and iron extraction yields were obtained as 75% and 80%, respectively under leaching conditions as follows: APS concentration 250 g/L; NaCl concentration 150 g/L; time 180 min; temperature 333 K; stirring speed 400 r/min; and L/S 250 mL/g.
Keywords: copper; chalcopyrite; oxidation; leaching; dissolution